2022
DOI: 10.1155/2022/2915157
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Nursing in Operating Room Combined with Intraoperative Heat Preservation Intervention on Prevention of Incision Infection and Improvement of Hemodynamics in Patients with Anterior Cruciate Ligament Injury and Reconstruction under Knee Arthroscopy

Abstract: Objective. To explore the effect of nursing in operating room combined with intraoperative heat preservation intervention on preventing incision infection and improving hemodynamics in patients with anterior cruciate ligament (ACL) injury and reconstruction under knee arthroscopy. Methods. About 200 patients with knee arthroscopic ACL reconstruction in our hospital from January 2019 to July 2021 were enrolled. The patients were randomly assigned into two groups: the control group and the study group. The forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…According to relevant studies, the proportion of patients experiencing postoperative shivering ranges from approximately 39 %–99 % [ 10 ]. Factors influencing the occurrence of postoperative shivering in complex PCNL primarily include temperature reduction, age, gender, pre-existing systemic conditions, infection status, surgical duration, and individual factors [ 11 ]. Research indicates that local anesthesia during the surgical process and postoperative analgesic consumption can lead to temperature reduction, making it one of the most common factors triggering shivering [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant studies, the proportion of patients experiencing postoperative shivering ranges from approximately 39 %–99 % [ 10 ]. Factors influencing the occurrence of postoperative shivering in complex PCNL primarily include temperature reduction, age, gender, pre-existing systemic conditions, infection status, surgical duration, and individual factors [ 11 ]. Research indicates that local anesthesia during the surgical process and postoperative analgesic consumption can lead to temperature reduction, making it one of the most common factors triggering shivering [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether in terms of preoperative publicity and education, venous access preparation, intraoperative attention to patients, cooperation with doctors, and prevention of postoperative complications, if the nursing work mode is not standardized, it is bound to affect the safety of operation and the rehabilitation of patients. Radiofrequency ablation of hypertrophic obstructive cardiomyopathy under the guidance of intracardiac ultrasound is a new and sophisticated operation in recent years [18]. At present, nurses lack a systematic understanding of the operation, the preparation of intraoperative instruments, and the prevention of surgical complications [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency ablation of hypertrophic obstructive cardiomyopathy under the guidance of intracardiac ultrasound is a new and sophisticated operation in recent years [18]. At present, nurses lack a systematic understanding of the operation, the preparation of intraoperative instruments, and the prevention of surgical complications [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%